The Iranian-Syrian relations and regional balance in the Middle East 1979-2019 - Ntarvis Tampar, Eleni (Πανεπιστήμιο Πελοποννήσου, 2021)
This thesis examines the Iranian-Syrian relations under the prism of Alliance Theory. Damascus and Tehran have built an alliance in order to deal with common threats and enemies. Despite their differences, Syria and Iran have formed a regional alliance for their survival in the Middle East. Furthermore, this thesis focuses on how their attempts to balance against prevailing threats have affected the developments in the regional system of the Middle East.
Keywords: Balance of power; Middle East; Syria; Iran; alliance; competition; regional hegemony; power vacuum; state and non state actors; balance of powers; Shia; Sunni; Middle East; national interests; Syrian-Iranian alliance